POLITICAL LIFE AND THE AGRARIAN QUESTION IN THE COLUMNS OF THE UKRAINIAN CERENIST NEWSPAPER “KHLIBOROBSKA PRAVDA”(THE SECOND HALF OF THE 1920S) - Глібіщук, Микола (My University, 2021)
Summing up, let’s focus on some of our considerations. First, the subject of political life and the agrarian question occupied an important place in the publications of the Ukrainian edition of the national cerenists “Khliborobska Pravda”. These topics, along with other current issues of the time (national, educational), aroused interest in the readership. Secondly, we believe that such thematic preferences were caused not only by the fact that the newspaper’s editors focused more on the Ukrainians of Northern Bukovina and Northern Bessarabia, but also on their ideological and political convictions. After all, the same editorial policy is observed in other publications of this political force, which were published in other territories of the Kingdom of Romania at that time. Third, we can state that such an emphasis on the publishing activities of the national cerenists and their consideration of ethnic specificity was, on the one hand, evidence of their political ambitions and aspirations to form their government. On the other hand, it reflects the realities of the “short twentieth century”, when the tools of “industrial civilization” (periodicals, radio, telegraph and other means of communication) were transformed into means of political struggle and the future of a political regime depended on their effective use.
Розділ монографії містить результати досліджень, проведених за грантом Націо-нального фонду досліджень України «Аграризм: селяноцентричний феномен Української революції 1917–1921 рр.» (реєстраційний номер 2020.02/0120).
Keywords: Revolution in Ukraine 1917-1921